Extreme Phytoplankton Blooms in the Southern Tropical Indian Ocean in 2011. Issue 4 (26th March 2020) - Liao, Xiaomei; Du, Yan; Wang, Tianyu; He, Qingyou; Zhan, Haigang; Hu, Shuibo; Wu, Guofeng
Abstract: This study investigates extreme phytoplankton blooms in the southern tropical Indian Ocean (TIO) in January–April 2011 using the extended ocean color products and in situ data. The amplitude of the blooms was approximately 4 times higher than the climatological value and 2 times higher than that in 1998–1999. The anomalous enhancement of surface chlorophyll‐ a concentration (Chl a ) was associated with the strong upwelling Rossby waves that forced by the extraordinary strong wind stress curl in the southeastern TIO during 2010–2011 La Niña, which was much stronger than that of 1998–1999 La Niña. The Rossby waves uplifted the thermocline, which was shoaled by more than 70 m relative to the climatology. The results of the nonlinear 1.5‐layer reduced‐gravity model further suggest that the thermocline variations are mainly due to the wind stress curl over the interior TIO. In the vertical direction, the Argo data show a distinct upward and westward propagation of subsurface cooling, indicating that the upwelling of cold nutrient‐rich waters leads to the abnormally high Chl a . The strong upwelling processes are also well captured by the Moored Array for African‐Asian‐Australian Monsoon Analysis and Prediction observations at 8°S, 80.5°E. Based on the climatological in situ nitrate data, the Rossby wave‐induced nitrate supply and potential new production at the mooring site are estimated. The potential f ratio ranges from 50% to 87% when the water brought to the surface is assumed to have originated from 60 to 200 m, thus indicating the dominant role of nutrient supply by the upwelling processes. Plain Language Summary: Taking advantage of extended ocean color products and observation from Argo and Moored Array for African‐Asian‐Australian Monsoon Analysis and Prediction, this study investigates extreme phytoplankton blooms in the southern TIO during the 2010–2011 La Niña event. The amplitude of the blooms was approximately 4 times higher than the climatological value and 2 times higher than that in another La Niña year 1998–1999. The anomalous enhancement of surface chlorophyll‐ a concentration was associated with the strong upwelling Rossby waves that forced by the extraordinary strong wind stress curl in the southeastern TIO during 2010–2011 La Niña. The in situ data reveal the dominant role of Rossby wave‐induced upwelling in triggering the extreme blooms in the southern TIO. Key Points: The extreme high chlorophyll‐ a in the southern TIO in 2011 is identified from two‐decade satellite observation The in situ data reveal the dominant role of Rossby wave‐induced upwelling in triggering the blooms La Niña‐induced wind stress curl in the southeastern TIO is much stronger in 2010–2011 than that in 1998–1999, accounting for the Rossby waves